Developmental profile at initial presentation in children with infantile spasms. (10th March 2019) - Sumanasena, Samanmali P; Wanigasinghe, Jithangi; Arambepola, Carukshi; Sri Ranganathan, Shalini; Muhandiram, Eindrini
Abstract : Aim: To describe the baseline developmental profile and influence of clinical and demographic factors on the developmental skills of infants diagnosed with infantile spasms. Method: Ninety‐five infants (55 males, 40 females) newly diagnosed with infantile spasms were recruited for a cross‐sectional, longitudinal study. All infants underwent Bayley Scales of Infant and Toddler Development assessments in the cognitive, receptive communication, expressive communication, and fine and gross motor developmental domains; they also underwent visual, auditory, and social behaviour assessments. Infants were categorized as 'early' (<6mo) or 'late' (≥6mo) presenters; if presented within 28 days, this was considered as 'early presentation', whereas a delay greater than 28 days was considered as a 'delay in presentation'. Antenatal, perinatal, and postnatal risk factors were identified. Results: Over 90% of infants showed impairment in all domains, with the majority having severe delay; 99% showed cognitive impairment. Delayed presentation was significantly associated with receptive communication delay (odds ratio [OR]=5.35; 95% confidence interval [CI]=1.05–27.32). Onset at 6 months or less influenced auditory (OR=2.8; 95% CI=1.16–6.8) and visual (OR=3.03; 95% CI=1.22–7.57) behaviours. Neonatal infections impacted both receptive (OR=1.12; 95% CI=1.04–1.2) and expressive communication (OR=1.08; 95% CI=1.02–1.14) delay. Neonatal seizures significantly influenced visual, auditory, and social impairments. Expressive communication and gross motor development shared common perinatal risk factors. Interpretation: Adverse developmental status at presentation, associated with delayed presentation and neonatal risk factors should alert clinicians to the surveillance of at‐risk infants and seek out timely interventions. What this paper adds: Ninety per cent of infants showed impaired cognitive, communication, and motor skills at presentation. Visual, auditory, and social behaviour impairments were significantly associated with perinatal risks. Visual, auditory, and social behaviour impairments were significantly associated with neonatal seizures. What this paper adds: Ninety per cent of infants showed impaired cognitive, communication, and motor skills at presentation. Visual, auditory, and social behaviour impairments were significantly associated with perinatal risks. Visual, auditory, and social behaviour impairments were significantly associated with neonatal seizures. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Lux on page 1244 of this issue. Video Podcast: https://www.youtube.com/watch?v=77rAyJDWKmk&t=1s Resumen: Perfil de desarrollo durante la presentación inicial de los espasmos infantiles en niños: Objetivo: Describir el perfil de desarrollo basal y la influencia de factores clínicos y demográficos sobre las habilidades de desarrollo en niños diagnosticados con espasmos infantiles. Metodo: Se reclutaron 95 niños recientemente diagnosticados con espasmos infantiles en una corte transversal, de un estudio longitudinal. Se realizaron Escalas de Bayley (Bayley Scales of Infant and Toddler Development) para el desarrollo de lactantes y preescolares a todos los niños, evaluando cognición, comunicación receptiva, comunicación expresiva, y los dominios del desarrollo motor, grueso y fino; también se sometieron a evaluaciones visuales, auditivas y de comportamiento social. Los niños fueron clasificados como presentación Temprana'(< 6 meses) o Tardía (≥ 6 meses); si los espasmos se presentaron dentro de los primeros 28 días, se consideró como presentación temprana, mientras que un retraso mayor de 28 días fue considerado como un retraso en la presentación. Se identificaron los factores de riesgo prenatales, perinatales y postnatales. Resultados: Más del 90% de los lactantes mostró discapacidad en todos los dominios, la mayoría con retraso severo; 99% mostró deterioro cognitivo. El retraso en la presentación está significativamente asociado con retraso en la comunicación receptiva (razón de probabilidades [OR]= 5, 35; 95% intervalo de confianza [CI]= 1, 05–27, 32). El inicio a los 6 meses o menos influenció en el comportamiento auditivo (OR = 2, 8; 95% CI = 1, 16–6, 8) y visual (OR = 3, 03; 95% CI = 1, 22–7, 57). Las infecciones neonatales impactaron tanto en el retraso de la comunicación receptiva (OR = 1, 12; 95% CI=1, 04–1, 2) como en la expresiva (OR =1, 08; 95% CI = 1, 02–1, 14). Las convulsiones neonatales influenciaron significativamente en discapacidades visuales, auditivas, y sociales. La comunicación expresiva y el desarrollo motor grueso tuvieron factores de riesgo perinatales comunes. Interpretación: Un estado de desarrollo adverso al momento de la presentación de espasmos infantiles, asociado con un retraso en la presentación y los factores de riesgo neonatal deben alertar a los clínicos a la vigilancia de niños en riesgo y buscar intervenciones oportunas. Resumo: Perfil de desenvolvimento na apresentação inicial em crianças com espasmos infantis: Xxx. Objetivo: Descrever o perfil de desenvolvimento inicial e a influência de fatores clínicos e demográficos nas habilidades do desenvolvimento de crianças diagnosticadas com espasmos infantis. Método: Noventa e cinco lactentes diagnosticados com espasmos infantis foram recrutados para um estudo transversal longitudinal. Todas as crianças foram submetidas a avaliações pela Escala Bayley de Desenvolvimento para bebes e crianças nos domínios Cognitivo, comunicação receptiva e expressiva, e desenvolvimento motor fino e grosso; eles também foram submetidos a avaliações: visual, auditivo e comportamento social. Os bebês foram categorizados como "precoces" (<6 m) ou "atrasados" (≥6 m); se apresentada no prazo de 28 dias, foi considerado como "precoces", enquanto que superior a 28 dias foi considerado como "atrasados". Fatores de risco pré‐natais, perinatais e pós‐natais foram identificados. Resultados: Mais de 90% dos lactentes apresentaram comprometimento em todos os domínios, sendo a maioria com atraso grave; 99% apresentaram comprometimento cognitivo. A apresentação tardia foi significativamente associada ao atraso na comunicação receptiva (odds ratio [OR] = 5, 35; intervalo de confiança de 95% [IC] = 1, 05‐27, 32). O início aos 6 meses ou menos influenciou os comportamentos auditivos (OR = 2, 8; 95% IC = 1, 16‐6, 8) e visuais (OR = 3, 03; IC95% = 1, 22‐7, 57). As infecções neonatais impactaram no atraso na comunicação receptiva (OR = 1, 12; 95% IC = 1, 04‐1, 2) e expressiva (OR = 1, 08; 95% IC = 1, 02‐1, 14). As convulsões neonatais comprometeram significativamente as áreas: visual, auditiva e social. Comunicação expressiva e desenvolvimento motor grosso ambos demostraram fatores de risco perinatais comuns. Interpretação: O estado de desenvolvimento adverso, associado à atraso na apresentação e fatores de risco neonatais devem alertar os clínicos para a vigilância de bebês de risco e buscar intervenções oportunas.